Shanghai on the Metro Spies, Intrigue, and the French Between the Wars. - Miller, Michael B. (Berkeley : University of California Press, 2020)
Secret agents, gun runners, White Russians, and con men--they all play a part in Michael B. Miller's strikingly original study of interwar France. Based on extensive research in security files and a mass of printed sources, Shanghai on the Métro shows how a distinctive milieu of spies and spy literature emerged between the two world wars, reflecting the atmosphere and concerns of these years. Miller argues that French fascina.
Intro -- Contents -- LIST OF ILLUSTRATIONS -- ACKNOWLEDGMENTS -- INTRODUCTION -- CHAPTER ONE. War -- CHAPTER TWO. Milieu -- CHAPTER THREE. Stories -- CHAPTER FOUR. Shanghai -- CONCLUSION -- NOTES -- BIBLIOGRAPHY -- INDEX
Description based upon print version of record.
JSTOR
Keywords: Intelligence service -- France -- History -- 20th century; Espionage -- France -- History -- 20th century; France -- History -- 1914-1940.; France -- Foreign relations -- 1914-1940.; Service des renseignements -- France -- Histoire -- 20e siècle.; Espionnage -- France -- Histoire -- 20e siècle.; France -- Histoire -- 1914-1940.; France -- Relations extérieures -- 1914-1940.; Diplomatic relations; Espionage; Intelligence service; France; 1900-1999; History